Gastrointestinal Anastomosis with Lumen Apposing Metal Stent - Deepanshu Jain; Ankit Chhoda; Abhinav Sharma; Shashideep Singhal (Korean Society of Gastrointestinal Endoscopy, 2018)
Gastric outlet obstruction, afferent or efferent limb obstruction, and biliary obstruction among patients with altered anatomy often require surgical intervention which is associated with significant morbidity and mortality. Endoscopic dilation for benign etiologies requires multiple sessions, whereas self-expandable metal stents used for malignant etiologies often fail due to tumor in-growth. Lumen apposing metal stents, placed endoscopically with the intent of creating a de-novo gastrointestinal anastomosis bypassing the site of obstruction, can potentially achieve similar efficacy, with a much lower complication rate. In our study cohort (n=79), the composite technical success rate and clinical success rate was 91.1% (72/79) and 97.2% (70/72), respectively. Five different techniques were used: 43% (34/79) underwent the balloon-assisted method, 27.9% (22/79) underwent endoscopic ultrasound-guided balloon occluded gastro-jejunostomy bypass, 20.3% (16/79) underwent the direct technique, 6.3% (5/79) underwent the hybrid rendezvous technique, and 2.5% (2/79) underwent natural orifice transluminal endoscopic surgery (NOTES)-assisted procedure. All techniques required an echoendoscope except NOTES. In all, 53.2% (42/79) had non-cautery enhanced Axios stent, 44.3% (35/79) had hot Axios stent, and 2.5% (2/79) had Niti-S spaxus stent. Symptom-recurrence was seen in 2.8%, and 6.3% had a complication (bleeding, abdominal pain or peritonitis). All procedures were performed by experts at centers of excellence with adequate surgical back up.